If \( \sum_{k=p}^{\infty} 4.3^{2-k}=\frac{2}{9} \), determine the value of \( p \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To solve the sum \( \sum_{k=p}^{\infty} 4.3^{2-k} = \frac{2}{9} \), we begin by rewriting the series: \[ \sum_{k=p}^{\infty} 4.3^{2-k} = 4 \sum_{k=p}^{\infty} 3^{2-k} \] Now we can rewrite \( 3^{2-k} \) as \( \frac{3^2}{3^k} \): \[ = 4 \sum_{k=p}^{\infty} \frac{9}{3^k} = 4 \cdot 9 \sum_{k=p}^{\infty} \frac{1}{3^k} \] Next, using the formula for the sum of a geometric series, where for \( |r| < 1 \): \[ \sum_{n=0}^{\infty} r^n = \frac{1}{1 - r} \] we find \( \sum_{k=p}^{\infty} \frac{1}{3^k} \). The series starts from \( k = p \): \[ \sum_{k=p}^{\infty} \frac{1}{3^k} = \frac{\frac{1}{3^p}}{1 - \frac{1}{3}} = \frac{\frac{1}{3^p}}{\frac{2}{3}} = \frac{1}{3^p} \cdot \frac{3}{2} = \frac{3}{2 \cdot 3^p} \] Now substitute this back into our expression for the sum: \[ \sum_{k=p}^{\infty} 4.3^{2-k} = 4 \cdot 9 \cdot \frac{3}{2 \cdot 3^p} = \frac{108}{2 \cdot 3^p} = \frac{54}{3^p} \] We set this equal to \( \frac{2}{9} \): \[ \frac{54}{3^p} = \frac{2}{9} \] Cross-multiplying gives: \[ 54 \cdot 9 = 2 \cdot 3^p \] Calculating \( 54 \cdot 9 \): \[ 54 \cdot 9 = 486 \] Thus, we have: \[ 486 = 2 \cdot 3^p \] Dividing both sides by 2: \[ 243 = 3^p \] Recognizing that \( 243 = 3^5 \), we find: \[ 3^p = 3^5 \implies p = 5 \] Therefore, the value of \( p \) is \[ \boxed{5} \]